The control of verticillium dahliae on artichokes bv chemical and non chemical soil disinfestation methods - Cebolla, Vicent; Navarro, C.; Miguel, Alfredo; Llorach, S.; Monfort, P. (2017)
Since some years ago, the globe artichoke (Cynara scolymus L.) crops of Benicarlo, at the north of Valencian Country (Alcachofa de Benicarlo, appellation of origin) frequently suffer a tracheomicotic syndrome produced by Verticillium dahliae. The fungus remains in the soil, after it is infested, for long periods of time and lasts even in rotations of crops intercalated between two successive of artichoke. The crop use to remain in the field for two consecutive seasons or even more, if it is allowed by the plant health condition. In order to study the effect of soil disinfestation for disease control several systems of soil disinfestation are compared. based on chemical systems like the successive application of 1,3-dichloropropene (Telone II emulsifiable) at 18 g/m(2) followed by metam-Na at 72 g/m(2), the mixture of 55.4% 1.3-dicholoropropene and 32.7% chloropicrin (Agrocelhone emulsifiable) at 40 g/m(2), all of them applied with the irrigation water, and physical methods like solarization with the addition of manure at 5 Kg/m(2) or combined method like solarization with metam-Na at 72 g/m2. Methyl bromide at 30 g/m(2) under VIF sheet and a non disinfested check was used. as reference. The studied parameters include, the biocidal effect in the soil and efficacy over weeds, plant vigour, yield in quantity and quality as well as mortality due to V. dahliae. Excellent results were reached, on the first season, with all the compared systems except the check which had a high mortality rate and heavy yield losses. The effects for wed control and plant vigour follow the same pattern. On the second season the results are similar to the first one, but some problem of plant death affected all the treatments. The studied systems for soil disinfestation ensures the healthiness and quality of crop at least by the first season, and facing the next phase out of methyl bromide as a consequence of Montreal Protocol, some chemical and physical alternatives are offered.